First demonstration of in-beam performance of bent Monolithic Active Pixel Sensors - Aglieri Rinella, Gianluca; Becht, Pascal; Blidaru, Mihail-Bogdan (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2022)
A novel approach for designing the next generation of vertex detectors foresees to employ wafer-scale sensors that can be bent to truly cylindrical geometries after thinning them to thicknesses of 20-40 μm. To solidify this concept, the feasibility of operating bent MAPS was demonstrated using 1.5cm×3cm ALPIDE chips. Already with their thickness of 50µm, they can be successfully bent to radii of about 2cm without any signs of mechanical or electrical damage. During a subsequent characterisation using a 5.4GeV electron beam, it was further confirmed that they preserve their full electrical functionality as well as particle detection performance. In this article, the bending procedure and the setup used for characterisation are detailed. Furthermore, the analysis of the beam test, including the measurement of the detection efficiency as a function of beam position and local inclination angle, is discussed. The results show that the sensors maintain their excellent performance after bending to radii of 2cm, with detection efficiencies above 99.9% at typical operating conditions, paving the way towards a new class of detectors with unprecedented low material budget and ideal geometrical properties.
Gesehen am 22.05.2023
Available online 10 January 2022, Version of Record 14 February 2022